(untitled) - Sarkan, Branislav (Doprava a spoje, 2011)
In the article there are analyzed data from the emission controls, which were made in the workplace of the Department of Road and Urban Transport from 2005 to 2009. We analyzed only gasoline engine vehicles and their production of CO and HC in emission controls based on the year of the vehicle production.